Integrasi Pendidikan Karakter Berbasis Nilai Islam dalam Sistem Pendidikan Modern di Indonesia - Herlina Putri; Fajar Ramadhan; Dewi Kartika (Al-Jinan : Jurnal Studi Islam, 2026)
This study investigates the integration of Islamic values-based character education within Indonesia's modern educational system. The background stems from an escalating moral crisis among Indonesian students—evidenced by rising cases of school violence, academic dishonesty, and social disintegration—which underscores the inadequacy of purely cognitive approaches to education. The purpose is to analyze the foundational principles, implementation models, and effectiveness of Islamic character education integrated within formal schooling frameworks. Employing a qualitative library research approach combined with hermeneutical and normative-analytical methods, this study examines relevant policy documents, curriculum frameworks, and contemporary scholarship on Islamic pedagogy published between 2020 and 2024. Findings reveal that Islamic values-based character education—anchored in tauhid, akhlaq, and amal salih—provides a comprehensive moral framework that significantly enriches secular character education approaches. The study concludes that systematic integration through curriculum design, teacher capacity building, and school culture transformation is essential for realizing the full potential of Islamic character education in modern Indonesian schools